Developing a Conceptual Framework using Exploratory Testing to Improve Software Quality in SME’s - Thangiah, Murugan; Basri, Shuib; Durai Dominic, Dhanapal (International Journal of Engineering and Technology, 2018)
In order to create quality software with standards and agreeing principles, the Small and Medium Software Enterprises (SMEâ€™s) faces many challenges and issues due to variety of reasons. Starting from the requirement analysis phase, the challenges emerge and continue until the project nears its completion, before being released to the customers or stakeholders. Various issues surfaced during the SDLC phases are identified and analyzed in the study. A Conceptual Framework using Exploratory Testing has been developed based on the study and the quantitative analyses were conducted using survey questionnaire. In this research paper the data analysis of the quantitative survey is conducted using Partial Least Square Structural Equation Modeling.Â The reliability and validity of the data is evaluated and presented in this paper which is essential to develop the conceptual framework. Further analysis of the survey questionnaire will be carried on and it will be reported in future work.Â